(untitled) (Journal of Chemical Engineering, 2013)
In this study, carboxymethyl-?-cyclodextrin (CM-?-CD) polymer modified Fe3O4 magnetic nanoparticles (CMPCD-MNPs) is fabricated and the feasibility of using these nanoadsorbents for removal of bisphenol A (BPA) and Pb2+ ions from aqueous solution was investigated. The properties of the particles were characterized by FTIR and TEM. The CM- ?-CD polymer grafted onto nanoparticle surface contributes to an enhancement of the adsorption capacity of Fe3O4 nanoparticles because of the strong complexation abilities of the multiple hydroxyl/carboxyl groups in CM-?-CD polymer with metal ions and of the hydrophobic cavity with organic contaminants through host-guest interactions. The adsorption of both BPA and Pb2+ ions onto CMPCD-MNPs was found to be dependent on pH. Adsorption equilibrium was achieved in 10-30 min and the adsorption kinetics of both contaminants is found to follow a pseudo-second-order kinetic model. Equilibrium adsorption data are fitted well by Langmuir isotherm model. Furthermore, these nanoadsorbents can be used as effective, separable and reusable materials for removal of both organic and inorganic contaminants from wastewater by magnetic separation systems. DOI: http://dx.doi.org/10.3329/jce.v27i1.15862 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 69-73